2022
DOI: 10.7150/ijbs.65589
|View full text |Cite
|
Sign up to set email alerts
|

HJURP Promotes Malignant Progression and Mediates Sensitivity to Cisplatin and WEE1-inhibitor in Serous Ovarian Cancer

Abstract: Ovarian cancer is the most lethal gynecological malignancy. Recurrence and chemoresistance are tough challenges leading to poor prognosis. HJURP is a molecular chaperone of CENP-A, which is associated with aggressive progression in multiple tumors. However, the function of HJURP in ovarian cancer has not been elucidated. In our study, we found HJURP was over-expressed in ovarian cancer and high expression of HJURP was correlated to unfavorable prognosis. HJURP knockdown could inhibit proliferation, metastasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 59 publications
(112 reference statements)
0
21
0
Order By: Relevance
“…A recent study revealed that mRNA and protein levels of HJURP in Ovarian serous cystadenocarcinoma (OV) tissues were significantly higher than those detected in normal fallopian tube; consistently, HJURP was also overexpressed in OV cell lines compared to normal ovarian epithelial cells ( Dou et al, 2022 ). High expression of HJURP was shown to be a negative risk factor for PFS by univariate and multifactorial Cox regression analyses, whereas Kaplan-Meier analysis indicated an association between high HJURP expression and worse prognosis, evaluated by both OS and PFS, in OV patients ( Dou et al, 2022 ). This is consistent with the previous findings by Li et al, who showed that increased expression of HJURP is an independent negative prognostic biomarker in patients with advanced serous OV ( Li et al, 2018 ) ( Table 1 ).…”
Section: Roles Of Hjurp In Tumorsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study revealed that mRNA and protein levels of HJURP in Ovarian serous cystadenocarcinoma (OV) tissues were significantly higher than those detected in normal fallopian tube; consistently, HJURP was also overexpressed in OV cell lines compared to normal ovarian epithelial cells ( Dou et al, 2022 ). High expression of HJURP was shown to be a negative risk factor for PFS by univariate and multifactorial Cox regression analyses, whereas Kaplan-Meier analysis indicated an association between high HJURP expression and worse prognosis, evaluated by both OS and PFS, in OV patients ( Dou et al, 2022 ). This is consistent with the previous findings by Li et al, who showed that increased expression of HJURP is an independent negative prognostic biomarker in patients with advanced serous OV ( Li et al, 2018 ) ( Table 1 ).…”
Section: Roles Of Hjurp In Tumorsmentioning
confidence: 99%
“…Silencing of HJURP significantly inhibited OV cell proliferation by inducing G0/G1 arrest and decreased also the migration and invasion potential of these cells. Of note, although HJURP silencing in OV cells did not promote apoptosis, this process was enhanced when combined with cisplatin treatment ( Dou et al, 2022 ). Interestingly, a positive association between HJURP expression and EMT was established by assays that showed that both vimentin and Slug expression was downregulated after HJURP knockdown, whereas Slug expression was significantly upregulated upon HJURP overexpression in SKOV3 cells ( Dou et al, 2022 ).…”
Section: Roles Of Hjurp In Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Public database. To validate our RNA-seq data, three datasets [GSE190688 (21), GSE54388 (22), GSE 40595 (23)] that analyzed DEGs between normal and high-grade serous ovarian cancer (HGSOC) samples were downloaded from the GEO Database (https://www.ncbinlm.nih.gov/geo/, accessed on December 20, 2021). An online public database, Kaplan-Meier Plotter (http://www.kmplot.com) which contains 10,293 lung, breast, gastric, and ovarian cancer samples to evaluate clinical outcomes of 54,675 genes were used to verify the prognostic significance of TMED9.…”
Section: Rna Sequencing Read Mapping and Gene Expression Analysismentioning
confidence: 99%
“…An inhibitor of HJURP has not yet been reported. HJURP has been demonstrated to play a significant role in numerous tumors, including prostate [ 108 ], breast [ 109 ], and ovarian cancers [ 110 ]. Therefore, it is essential to further investigate the function and mechanism of HJURP in tumors of the digestive tract.…”
Section: Histone Chaperones In Digestive Cancersmentioning
confidence: 99%